ANALISIS HUBUNGAN ENJOYMENT, ENTERTAINMENT, EDUCATION, FLOW DAN DESIGN BACKGROUND DALAM VIRTUAL TOURISM SELAMA COVID-19 - Nur Amalyna Yusrin; Natasya Sugianto (Universitas Multimedia Nusantara, 2021)
Abstract- COVID-19 has a significant impact for Indonesian tourism industry and MSMEs (Micro, Small, Medium, Entreprises) where are strong leaning on direct interaction. This condition causes has a significant impact on the decline of national tourism economy. It impacts to a contraction of 88.82% in 2020 which increases the risk of loss by IDR 54.6 trillion if it occurs during the year. It is as a result government’s policy to keep the distance to break the COVID-19 spread however, tourism well known as an industry where cannot be separated by human touch and visitors direct experience. In this digital development era, virtual tourism becomes the alternative solution to reduce contraction rate implemented by tourism entrepreneur and the Indonesian Ministry of Tourism and Creative Economy. When talking about technology, we will discuss how it is executed in the present and the development of its implementation for the next 10 years. Existing research focuses on the marketing elements of virtual tourism, therefore, it is important to analyse which elements in the virtual tourism experience are able to attract the attention of tourists for continuance using virtual tourism. Researcher implement quantitative methods by distributing questionnaires to 308 respondents to millennial labor force in urban cities. Researchers used TAM (Theory of Acceptance Model) to see the effect of enjoyment, entertainment, education as Perceived Ease of Use (PEOU) and Flow and Design Background as Perceived Usefuless (PU). The results of this study indicates Education, Flow and Design Background elements have direct positive effect on increasing tourist attention using Virtual Tourism. This research is expected to be able to contribute to the development of virtual tourism technology and how it is implemented in Marketing 5.0 Keywords: Virtual Touris;, Continuance Purchase Intention; Percevived Eased of Use; Perceived of Usefulness